Surgical planning for a complex double‐outlet right ventricle using 3D printing. Issue 5 (19th March 2017) - Bhatla, Puneet; Tretter, Justin T.; Chikkabyrappa, Sathish; Chakravarti, Sujata; Mosca, Ralph S.
Abstract : Rapid prototyping may be beneficial in properly selected cases of complex congenital heart disease, providing detailed anatomical understanding that helps to guide potential surgical and cardiac catheterization interventions. We present a case of double‐outlet right ventricle, where the decision to obtain a three‐dimensional printed model helped for better understanding of the anatomy, with the additional advantage of surgical simulation in planning the surgical approach and type of surgical repair.